2004
DOI: 10.3354/cr026199
|View full text |Cite
|
Sign up to set email alerts
|

Dry spell frequencies and their variability over southern Africa

Abstract: Marked interannual fluctuations in rainfall are a fundamental aspect of southern African climate. This study uses dry spell frequency (DSF) to assess spatial and temporal patterns in the consistency of rainfall during the mid-summer (DJF) season and their relationships to interannual drought occurrences in southern Africa. The Climate Prediction Center Merged Analysis of Precipitation (CMAP) pentad data are used to identify dry spells, which are defined here as a pentad with mean daily rainfall less than 1 mm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
157
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 32 publications
13
157
1
Order By: Relevance
“…Future rainfall scenarios, however, are rather uncertain in this region due to the complexity of the physical mechanisms responsible for Sahelian rainfall patterns (Christensen et al, 2007;Giannini et al, 2008). Furthermore, Usman and Reason (2004) analysed a longer time-series and showed that the most significant increases in occurrences of heavy rainfall events were observed in central Namibia and Angola in the west. Our study indicates that this trend continued from 2001 until 2010.…”
Section: Rainfall Patternsmentioning
confidence: 99%
“…Future rainfall scenarios, however, are rather uncertain in this region due to the complexity of the physical mechanisms responsible for Sahelian rainfall patterns (Christensen et al, 2007;Giannini et al, 2008). Furthermore, Usman and Reason (2004) analysed a longer time-series and showed that the most significant increases in occurrences of heavy rainfall events were observed in central Namibia and Angola in the west. Our study indicates that this trend continued from 2001 until 2010.…”
Section: Rainfall Patternsmentioning
confidence: 99%
“…For agricultural practices, the consistency with which the basic minimum of needed rainfall is received is more important than the total received over time. Crops are more likely to do well with uniformly spread 'light' rains than with a few 'heavy' rains interrupted by dry periods (Usman and Reason, 2004;Hachigonta and Reason, 2006). The timing of rainfall onset, duration, and cessation relative to the cropping calendar is more fundamental to crop viability than focusing on total seasonal rainfall alone.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of CA on infiltration and soil water Rainfall distribution patterns during the growing season in Southern Africa are characterized by mid-season dry spells 63,64 . Thus, higher infiltration rates under CA and surface crop residue retention have the potential to buffer growing crops against intermittent periods of drought stress.…”
Section: Conservation Agriculture In Southern Africamentioning
confidence: 99%